BEM-based algorithm for composite materials with Gurtin-Murdoch interfaces: Error analysis and effective parameters - Han, Zhilin; Gu, Yankai; Liang, Yongcheng; Zheng, Xingwei (Mechanics of advanced materials and structures, 2022)
The effective parameters of the composite materials with Gurtin-Murdoch ((G-M) interfaces are analyzed by standard boundary element method (BEM)-based equivalent inhomogeneity technique (EIT). The physical quantities all over the domain are first compared with the analytical and semi-analytical results to validate accuracy. The effective parameters are then obtained by the present numerical EIT. Since interactions have been considered, we believe our results are more accurate than traditional estimations, such as the generalized self-consistent model (GSCM). Due to the numerical treatment is performed to the present method is more flexible to simulate the effective parameters of clusters with complex geometries.